(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the fundamental aspects of syllables, highlighting their structure, formation, and the rules guiding their separation. A syllable, the smallest unit of sound in language, comprises essential parts: the onset, nucleus, and coda. These components contribute to a word’s overall pronunciation and rhythm, and each syllable centers around a vowel sound. The article outlines rules of syllable separation in English, such as how consonants and vowels are divided within words and how linguistic elements like prefixes and clusters affect syllabification. By understanding these rules, readers can improve their pronunciation, reading, spelling, and comprehension skills. The article emphasizes that syllables are not only critical for spoken language but also play a vital role in reading fluency and effective communication.